The Drive toward Universal Health Coverage - Kim, Young Eun; Loayza, Norman V. (World Bank, Washington, DC, 2018)
Universal health coverage is a social goal that enables everyone to receive the quality health care they need, irrespective of ability to pay, without suffering financial hardship in the process. To move toward that goal, policy makers should address three main considerations: the population to be covered, the health services to be provided, and the financing mechanism to be used. Successful cases show that to achieve universal health coverage, a change of perspective is essential, from seeing health care benefits as a contingent good to considering them as an essential public service. While expanding the demand for health care is necessary, improving the quantity and quality of the supply of health services is essential. Getting diverse stakeholders to cooperate, making cost-efficient and people-centered choices, and ensuring fiscal sustainability are needed to expand health coverage for everyone who needs it.